An Explanatory Study of the Parameters to Be Measured From EMG Signal (International Journal of Engineering and Computer Science, 2013)
Electromyography (EMG) is the analytical study of electrical activity produced by skeletal muscles. EMG is an example of modern human computer interaction which can be used in the field of medicines and engineering. Through this paper we are going to discuss about standard parameters which can be used to analyse EMG-Surface EMG (SEMG) /surface scanning EMG signals because these parameters reflects the physiological activity of the motor unit. In this paper, we will also discuss the history of EMG, types of EMG, characteristics of EMG signal, muscles involved in movements of hand, parameters which are used to analyse EMG signal, variety of applications where EMG signals can be used. This paper will provide the researchers a good understanding of EMG signal and its analysis. This knowledge will help them to develop more powerful and efficient applications. Keywords— EMG (Electromyography), Muscles of Hand, Standard Parameters, Threshold Detection, Applications.